Genetic markers of children asthma: predisposition to disease course variants - M. V. Smolnikova; Ed. W. Kasparov; M. A. Malinchik; K. V. Kopylova (Вавиловский журнал генетики и селекции)
Asthma is a heterogeneous and often difficult to treat condition that results in a disproportionate cost to healthcare systems. Children with severe asthma are at increased risk for adverse outcomes including medication-related side effects, life-threatening exacerbations, and impaired quality of life. An important therapeutic focus is to achieve disease control, which is supposed to involve a personalized approach to treatment of asthma of any severity. Asthma is a multifactorial disease with a significant genetic determinant, however, the inheritance of asthma has not been fully elucidated. Polymorphic genes of inflammatory mediators, including cytokines, play an important role in developing various disease forms. In the current study, large-scale original data on the prevalence of cytokine gene genotypes (IL2, IL4, IL5, IL6, IL10, IL12, IL13, IL17A, IL31, IL33, IFNG, TNFA) among Russian children with asthma in Krasnoyarsk region have been obtained. Genotyping was carried out using real-time PCR. We identified markers predisposing to the development of different variants of the course of childhood asthma: the CT genotype and T allele of IL4 rs2243250 are associated with asthma (p < 0.05), especially in mild asthma and in controlled asthma. The TT genotype and allele T of IL13 rs1800925 are associated with severe and uncontrolled asthma (p < 0.05). The AA genotype of IL17A rs2275913, the TT genotype of IFNG rs2069705 and allelic A variants of TNFA rs1800629 are associated with mild asthma, and the TT genotype of IFNG rs2069705 is additionally associated with controlled asthma. The results obtained will supplement information on the prevalence of polymorphic variants of the cytokine genes in the Russian population and in asthma patients with different disease courses, which is likely to be used in order to shape a plan for Public Health Authority to prevent the development of severe uncontrolled asthma and to optimize personalized therapy.